2016
DOI: 10.2135/cropsci2016.01.0026
|View full text |Cite
|
Sign up to set email alerts
|

Association of New Mutant Allele, w4nw, at W4 Locus with Near‐White Flower Color in Soybean

Abstract: An ethyl methanesulfonate‐induced mutant (PE1033) with near‐white flowers was isolated from the soybean [Glycine max (L.) Merr.] cultivar Pungsannamul with purple flowers that had the W1w3W4 genotype. In the present study, we aimed to investigate the genetic and molecular bases of the flower color variation displayed by the PE1033 mutant. Analyses of genomic sequences and reverse transcription–polymerase chain reaction (RT‐PCR) revealed that the color variation of PE1033 flowers originated from a recessive mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…(C) The tree constructed using genome sequences ranging from the primer sequence ACTTGATTTCAGCCATGGTA to stop codon of DFR2. Most of w4 mutants investigated were derived from ethyl methanesulfonate-treated populations or revertant mutants from T322 containing an active CACTA-like transposable element, except for cultivar Laredo (Hartwig and Hinson, 1962;Palmer et al, 1989;Xu et al, 2010;Yan et al, 2014;Park et al, 2016). Genbank accession numbers of DFR2 sequences retrieved from GenBank are KU376490 (Pungsannamul), AB872216 (Clark), KX077985 (CW12700), KX077986 (IT182932), and AB872217 (kw4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(C) The tree constructed using genome sequences ranging from the primer sequence ACTTGATTTCAGCCATGGTA to stop codon of DFR2. Most of w4 mutants investigated were derived from ethyl methanesulfonate-treated populations or revertant mutants from T322 containing an active CACTA-like transposable element, except for cultivar Laredo (Hartwig and Hinson, 1962;Palmer et al, 1989;Xu et al, 2010;Yan et al, 2014;Park et al, 2016). Genbank accession numbers of DFR2 sequences retrieved from GenBank are KU376490 (Pungsannamul), AB872216 (Clark), KX077985 (CW12700), KX077986 (IT182932), and AB872217 (kw4).…”
Section: Discussionmentioning
confidence: 99%
“…Although flower colors were predominantly determined by the W1 locus in the current G. max population, numerous studies have shown that mutations at the W4 locus were responsible for changes in flower colors, ranging from dilute purple to near white. Most of w4 mutants investigated were derived from ethyl methanesulfonate-treated populations or revertant mutants from T322 containing an active CACTA-like transposable element, except for cultivar Laredo (Hartwig and Hinson, 1962;Palmer et al, 1989;Xu et al, 2010;Yan et al, 2014;Park et al, 2016). Mutation at the w4 locus in Laredo appeared to be stable because a single-nucleotide substitution abolished the 5¢ splice site of the fourth intron, resulting in the expression of a truncated polypeptide.…”
Section: Discussionmentioning
confidence: 99%
“…In soybean, DFR-encoding genes co-segregated with two genetic loci, namely, W3 ( DFR1 ) and W4 ( DFR2 ), and they were epistatic to each other under the W1 allelic background [ 10 , 11 ]. Double mutations in W3 and W4 , i.e., w3 w4 , led to the development of near-white flowers in soybean [ 11 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…These authors found that DFR1 is highly expressed in a W3 allelic background but is barely expressed in w3 and also proposed that, among several polymorphisms detected in the genomic sequence of the w3 allele, a noteworthy insertion and deletion (indel) of 311 bp in the 5′‐upstream region might cause the disruption of DFR1 expression. With respect to the W4 locus in the w3 recessive allelic background, six different mutant alleles have been reported, namely, w4 , w4‐m , w4‐dp , w4‐p , w4‐lp , and w4‐nw , which produce near‐white, variegated, dilute purple, pale purple, light purple, and near‐white flowers, respectively (Palmer et al, 1989; Groose and Palmer, 1991; Xu and Palmer, 2005; Xu et al, 2010; Yan et al, 2014; Park et al, 2016).…”
mentioning
confidence: 99%
“…To date, only six accessions have been reported to have white or white‐hued flowers. Genetic and molecular studies have revealed that flower color in five of these six accessions is related to mutations at the W1 locus (Chen and Nelson, 2004; Takahashi et al, 2010, 2012; Park et al, 2016). In addition, Yan et al (2014) showed that the near‐white color of the G. soja accession kw4 is controlled by a recessive allele of the W4 locus, which encodes DFR2.…”
mentioning
confidence: 99%